1 Validity and reliability of short-term heart-rate variability from disposable electrocardiography leads. (21st November 2022) - Okwose, Nduka Charles; Russell, Sophie Lauren; Rahman, Mushidur; Steward, Charles James; Harwood, Amy Elizabeth; McGregor, Gordon; Ninkovic, Srdjan; Maddock, Helen; Banerjee, Prithwish; Jakovljevic, Djordje G
Abstract : Background: The evaluation of heart rate variability (HRV) has become increasingly common, as a simple, non-invasive measure that is sensitive to physiological changes and can help to structure exercise training programmes, adaptation, and recovery. Novel single-use electrocardiography (ECG) leads have been developed to monitor HRV in clinical and rehabilitation settings. Aim: This study assessed the validity and reliability of short-term HRV measures obtained from disposable ECG leads. Methods: Thirty healthy subjects (mean age 33±10 years; 9 females) underwent five-minute resting HRV assessments using disposable (single use) ECG (Kendall DL TM Cardinal Health, USA) and a standard, reusable ECG leads (CardioExpress, Spacelabs Healthcare, USA). Time and frequency domain data from were analysed using Intraclass correlation coefficient (ICC) and Bland-Altman (B-A) analyses with p values <0.05 regarded as significant. Results: The ICC with 95% confidence interval (CI) between disposable and reusable leads was excellent for time domain (R-R interval (ms); 0.99 (0.91, 1.00), root mean square of successive normal R-R interval differences (RMSSD) (ms); 0.91 (0.76, 0.96), SD of normal-to-normal R-R intervals (SDNN) (ms); 0.91 (0.68, 0.97) and frequency domain (Low Frequency (LF) normalised units (nu); 0.90 (0.79, 0.95), High Frequency (HF) nu; 0.91 (0.80, 0.96), LF power (ms 2 ); 0.89 (0.62, 0.96), HF power (ms 2 ); 0.90 (0.72, 0.96) variables. The mean difference and upper and lower limits of agreement between disposable and reusable leads for time (<2.5±1.4%) and frequency (<5±1%) domain measures were acceptable. Repeated measures using disposable leads demonstrated excellent reproducibility (ICC 95% CI) for R-R interval (ms); 0.93 (0.85, 0.97), RMSSD (ms); 0.93 (0.85, 0.97), SDNN (ms); 0.88 (0.75, 0.95), LF power (ms 2 ); 0.87 (0.72, 0.94), and HF power (ms 2 ); 0.88 (0.73, 0.94) with coefficient of variation ranging from 2.2%-5%. Conclusion: Single-use Kendall DL TM ECG leads demonstrate a valid and reproducible tool for assessment of HRV. Disposable leads may also play an important role in infection control in clinical and rehabilitation settings.